Evaluating the impact of concentrated match scheduling in college volleyball during the COVID-19 pandemic - Mitchell, M.; Wachsman, Y.; Fine, M. (The Sport Journal, 2021)
Athletic conferences worked to lower the cost of delivering athletic programs while operating during the COVID-19 global pandemic. One strategy was the use of concentrated schedules for competitions. For example, the Sun Belt Conference focused on divisional play and a concentrated schedule for women`s volleyball for the 2020 season. Schools played three matches in a two-day period against the same team. This practice lowered travel costs and isolated player contact in the event of needed contact tracing as part of player safety protocols. This study evaluates the impact of this scheduling format on player performance and the overall quality of competition. Gathering data from the box scores from all Sun Belt Conference volleyball matches, the impact of player fatigue (daily and cumulative) is not present in the team statistics. Player performance and the overall quality of team play did not decline, even when playing three matches in a two-day period. Conference personnel and university athletic administrators may take comfort that their efforts to lower costs and ensure player safety during a global pandemic did not affect player performance and the overall quality of competition. It remains to be seen if this new scheduling approach will be used in the post-COVID period in women`s volleyball and possibly expanded to other sports. The need to control/lower operating costs will not disappear. This constraint may lead to the adoption of new conference scheduling formats in the future.